2017
DOI: 10.1007/s10973-017-6848-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative use of thermal analysis for the investigation of the properties of granules during fluid bed melt granulation

Abstract: This study describes a novel approach for the use of thermal analysis to study the aftermath of the fluid bed melt granulation process and to depict the growth mechanism of the granules by quantifying the enthalpies of the granules at every physicochemical change using DSC and their mass loss through TG coupled to MS for a qualitative determination of the composition and amount of the evolved gases for the corresponding fragment ion. The experiments were made in-situ with lactose monohydrate and two viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…This corresponds to the decomposition of the materials or PEG chains, carbonaceous material originating from the decomposition of the high molecular weight polymer (PEG6000). These results concur with the previously reported weight loss (98.79%) of PEG6000 [53]. Jayaramudu et al [33] also reported a similar weight loss of 95.97% for PEG6000 in the same temperature range.…”
Section: Thermogravimetric Properties Of Molp and Sdmolpssupporting
confidence: 92%
“…This corresponds to the decomposition of the materials or PEG chains, carbonaceous material originating from the decomposition of the high molecular weight polymer (PEG6000). These results concur with the previously reported weight loss (98.79%) of PEG6000 [53]. Jayaramudu et al [33] also reported a similar weight loss of 95.97% for PEG6000 in the same temperature range.…”
Section: Thermogravimetric Properties Of Molp and Sdmolpssupporting
confidence: 92%
“…They are appropriate to use (fibers or granules as basic materials) for the microencapsulation of drugs having short biological half-life but frequent administration. It is important the long-term stability of controlled-release dosage forms too [7,[41][42][43][44]. The indiscriminate use of antifungal agents has led to the advancement of microorganisms tolerant to the various drugs used in the market [45].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, manufacturing technique is useful to create physical models for different medical and pharmacological application based on three-dimensional (3D) computed data [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. All these applications strongly rely on material properties such as mechanical and thermal characteristics, biocompatibility, and in the last years, the antibacterial capability became important factor because of the undesirable infections.…”
Section: Introductionmentioning
confidence: 99%